Generation of quantum entanglement in superposed diamond spacetime - Xiaofang Liu; Changjing Zeng; Jieci Wang (European Physical Journal C: Particles and Fields)
Abstract A comprehensive study integrating the microscopic structure of spacetime and the principle of quantum superposition is capable of offering a fundamental bottom-up approach for understanding the quantum aspect of gravity. In this paper, we present a framework for the superposition of spacetime structures in the causal diamond spacetime and analyze the behavior of quantum entanglement generated by spacetime superposition from the perspective of relativistic quantum information. For the first time, we combine the concept of spacetime superposition with causal diamonds and derive the analytical expression of the Unruh-diamond vacuum state for Dirac fields in the causal diamond spacetime. Based on this, we analyze both initially correlated and uncorrelated modes in superposed and classical causal diamond spacetimes, and quantifying how quantum thermal effects arising from spacetime structure alter entanglement. Our findings reveal that quantum entanglement degrades in classical diamond spacetime, while the superposed structure generates additional entanglement resources between modes in superposed diamond spacetimes. From a quantum information perspective, our results suggest that the characteristics of spacetime structural manifestations can serve as valuable resources for performing quantum information processing tasks.